Determination of the cationic distribution in oxidic thin films by resonant X‐ray diffraction: the magnetoelectric compound Ga2−xFexO3. Issue 4 (27th July 2016) - Lefevre, Christophe; Thomasson, Alexandre; Roulland, Francois; Favre-Nicolin, Vincent; Joly, Yves; Wakabayashi, Yusuke; Versini, Gilles; Barre, Sophie; Leuvrey, Cedric; Demchenko, Anna; Boudet, Nathalie; Viart, Nathalie
Abstract : The determination of the cationic distribution in complex oxide thin films has been shown to be possible through a methodological processing of resonant X‐ray diffraction data with a crystallography‐based approach. Abstract : The cationic distribution is decisive for both the magnetic and electric properties of complex oxides. While it can be easily determined in bulk materials using classical methods such as X‐ray or neutron diffraction, difficulties arise for thin films owing to the relatively small amount of material to probe. It is shown here that a full determination of the cationic site distribution in thin films is possible through an optimized processing of resonant elastic X‐ray scattering experiments. The method is illustrated using gallium ferrite Ga2− x Fe x O3 samples which have been the focus of an increasing number of studies this past decade. They indeed represent an alternative to the, to date, only room‐temperature magnetoelectric compound BiFeO3 . The methodology can be applied to determine the element distribution over the various crystallographic sites in any crystallized system.